Incidence of Post-Operative Delirium in Orthogeriatric Population: General Anaesthesia versus Spinal Anaesthesia: An Observational Study - Aqsa Aman Katto; Robyna Khan; Syed Akmal Sultan; Twahir Kalekhan Dina (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative delirium (POD) is the acute disfunction of cognition in post-surgical period affecting older patients. Aim: To find comparison between frequencies of postoperative delirium in general versus spinal anaesthesia. Methods: This prospective observational study was done at the Department of Anaesthesiology, The Aga Khan University Hospital, Karachi, from August 2020 to July 2021. Demographic data was collected on weight, ASA level, surgical procedure, and type of anaesthesia. Pre- and postoperative cognition level was recorded using the Confusion-Assessment-Method scale (CAM). Quantitative variables were presented as descriptive statistics with mean and standard deviation, and qualitative variables were expressed as percentages and frequency with a P value ≤0.05 as significant. Results: A total of 151 patients were enrolled with a mean age of 65.98±6.48 years, duration of surgery 126.50±75.42 min, and weight 71.42±7.38 kg. Males constituted 95(62.9%) and 56(37.1%) were female. Out of 151 patients, 33(21.9%) patients developed postoperative delirium, of which 31(93.9%) patients received G/A and 2 (6.1%) patients received spinal anaesthesia. ASA grade ≥II being the only statistically major factor (P value=0.001) increasing risk of postsurgical delirium. Conclusion: A sizeable number of subjects have developed postsurgical delirium in an orthogeriatric population. Patients over the age of 75 with the history of comorbidities, ASA grade ≥ II, and use of general anaesthetics have a higher incidence of developing postsurgical delirium. Keywords: Post-operative delirium, general anaesthesia, spinal anaesthesia, orthogeriatric